On the orientational relief of the intermolecular potential and the structure of domain walls in fullerite C60 - Khalack, Julia M.; Loktev, Vadim M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A simple planar model for an orientational ordering of threefold molecules on a triangular lattice modeling a close-packed (111) plane of fullerite is considered. The system has 3-sublattice ordered ground state which includes 3 different molecular orientations. There exist 6 kinds oforientational domains, which are related with a permutation or a mirror symmetry. Interdomain walls are found to be rather narrow. The model molecules have two-well orientational potential profiles, which are slightly effected by a presence of a straight domain wall. The reason is a stronger correlation between neighbor molecules in the triangular lattice versus the square lattice previously considered. A considerable reduction (up to one order) of the orientational interwell potential barrier is found in the core regions of essentially two-dimentional potential defects, such as a three-domain boundary or a kink in the domain wall. For ultimately uncorrelated nearest neighbors the height of the interwell barrier can be reduced even by a factor of 102.